Predictors of Leadership Competencies Among Nurse Executives in the Kingdom of Saudi Arabia - Alshamlani,Yousef; Alanazi,Naif; Alhamidi,Sami; Alanazi,Raeed; Alenezi,Atallah; Adalin,Norisk; Alyousef,Seham; Tumala,Regie (Journal of Healthcare Leadership, 2024)
Yousef A Alshamlani,1,* Naif H Alanazi,2,* Sami A Alhamidi,2,* Raeed A Alanazi,2,* Atallah Alenezi,3,* Norisk M Adalin,1,* Seham M Alyousef,2,* Regie B Tumala2,* 1Nursing Department, King Saud University Medical City, Diriyah, Riyadh, Kingdom of Saudi Arabia; 2College of Nursing, King Saud University, Diriyah, Riyadh, Kingdom of Saudi Arabia; 3Nursing Department, College of Applied Medical Sciences, Shaqra University, Shaqra, Kingdom of Saudi Arabia*These authors contributed equally to this workCorrespondence: Regie B Tumala, College of Nursing, King Saud University, Diriyah, Riyadh, 11421, Kingdom of Saudi Arabia, Tel +966554773976, Email rtumala@ksu.edu.saBackground: Awareness and development of nurse executivesâ€™ leadership competencies has been considered a key strategy for the success of healthcare organizations. However, only a few studies about nurse executivesâ€™ leadership competencies are available in the literature, and no study has been conducted about the topic within Saudi Arabian context. The aim of this study was to assess the leadership competencies of nurse executives and the predictors of these competencies.Methods: This quantitative study used a descriptive, cross-sectional, and correlational design. The study recruited a total convenience sample of 136 nurse executives who voluntarily consented to participate. The respondents self-rated the online survey, â€œLeadership Competency Assessment Tool: Self-Assessment.â€ Data collection was conducted between September 2022 and November 2022. Test of correlation and multiple regression analyses were conducted.Results: The overall mean score of nurse executivesâ€™ leadership competencies was 3.38 out of 5.0, which was below the level of having excellent leadership competencies. Four dimensions had mean scores below the level of having excellent leadership competencies, namely, communication and relationship building (3.48), knowledge of the healthcare environment (3.29), ...